TAX PLANNING AND LIQUIDY IMPACT ON EARNINGS MANAGEMENT : THE MODERATING ROLE OF FIRM SIZE - Audrey Velma Sasikirana; Melianawati Melianawati; Ubaydillah Azzam; Elyzabet Indrawati Marpaung (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study explores how tax planning and liquidity relate to earnings management and whether firm size strengthens or weakens these relationships. Managers may be encouraged to use discretion in financial reporting due to conflicting interests with shareholders, which may result in earning management techniques. This research adopts a quantitative technique to investigate secondary data from enterprises in the raw materials sector that were listed on the Indonesia Stock Exchange (IDX) in 2018-2024. 32 of the 114 firms in the population met the sample criteria, resulting in 224 firm-year observations. The hypotheses were assessed using panel data regression, and the Chow, Hausman, and Lagrange Multiplier (LM) tests were used to choose a model. The results indicate that the random effect model is the most appropriate for the investigation. According to empirical studies, tax planning affects earnings management, but liquidity does not. Furthermore, whereas firm size does not attenuate the link between liquidity and earning management, it does strengthen the relationship between tax planning and earnings management. . The implications of this study suggest that understanding tax planning strategies and firm size is important for stakeholders in assessing the quality of reported earnings. These findings are expected to be useful for regulators, investors, and company management in improving the transparency and quality of financial reporting.